Analysis of Education Socialization for Environmental Management Due to Clay Mining Activities for the Peoples - Nila Rahmad Defita; Eri Barlian; Dedi Hermon (Postgraduate School, Universitas Negeri Padang, 2022)
Mining activities are human activities that utilize natural resources to produce products used in everyday life. Mining activities trigger the damage that occurs, ranging from changes in topography and loss of vegetation cover. Environmental damage caused by mining activities has now become an international issue because of the widely reported regional and global assessments of various mining commodities. However, only a few studies have published environmental damage on a detailed and local scale. The research was designed to determine the environmental damage that occurred in Gunung Sarik Village, Kuranji Sub-district with a quantitative descriptive method in the field. The mining commodity is clay which is used as a raw material for bricks as well as a mixture for making cement. Parameters observed included abiotic, biotic, and cultural aspects. To determine the level of damage to the abiotic and biotic aspects, the grading method is used, so that the damage that occurs is included in the moderate damage category. This is caused by errors in mining procedures that do not pay attention to ecological aspects. Changes in the landscape, the slope of the slopes, the height of the excavation cliffs, and the absence of vegetation cause physical damage that triggers landslides. Economically, there was no negative impact on society. A lack of ecological understanding underlies public ignorance about the environmental damage caused by mining activities. The results of the analysis of the level of environmental damage in Gunung Sarik Village, a strategy for managing environmental damage due to mining was prepared using SWOT analysis.